Knockdown of long non-coding RNA TUG1 depresses apoptosis of hippocampal neurons in Alzheimer’s disease by elevating microRNA-15a and repressing ROCK1 expression - Li, Xia; Sheng-Wu, Wang; Xi-Ling, LI; Feng-Yuan, Yu; Hai-Ming, Cong (Inflammation research, 2020)
ObjectiveMany studies have already suggested the role of long non-coding RNAs (lncRNAs) in Alzheimer’s disease (AD), but the functions of lncRNA Taurine Upregulated Gene 1 (TUG1) in AD have been scarcely discussed. This study aims to verify how TUG1 affects hippocampal neurons in AD through modulation of microRNA-15a (miR-15a)/Rho-associated protein kinase 1 (ROCK1).MethodAD mice was modeled through injection of β-amyloid 25-35 (Aβ25-35) into the lateral ventricle. After modeling, the mice were injected with altered TUG1 and/or miR-15a agomir lentiviruses. The spatial learning ability and memory ability of mice were detected through Morris water maze test. Hippocampal neuronal apoptosis and oxidative stress indicators in AD mice were then detected. The hippocampal neuron AD model was induced by Aβ25-35. Next, the neurons were, respectively, transfected with altered TUG1 vector and/or miR-15a mimics to determine the proliferation inhibition and apoptosis of hippocampal neurons. The interactions between TUG1 and miR-15a, and between miR-15a and ROCK1 were assessed using bioinformatic prediction, dual luciferase reporter gene assay and RNA-pull-down assay.ResultsIn the animal models, Aβ25-35-induced mice exhibited decreased spatial learning and memory ability, obvious pathological injury, promoted hippocampal neuronal apoptosis and decreased antioxidant ability. TUG1 silencing and miR-15a elevation improved spatial learning ability and memory ability, ameliorated pathological injury, depressed neuronal apoptosis, and strengthened antioxidant ability of hippocampal neurons in AD mice. In cellular models, Aβ25-35-treated hippocampal neurons presented inhibited neuronal viability and promoted neuronal apoptosis. TUG1 silencing and miR-15a elevation increased viability and limited apoptosis of Aβ25-35-treated hippocampal neurons. TUG1 specifically bound to miR-15a, and miR-15a targeted ROCK1.ConclusionCollectively, this study reveals that TUG1 knockdown restricts apoptosis of hippocampal neurons in AD by elevating miR-15a and suppressing ROCK1 expression, and provides a new therapeutic target for AD treatment.